Political philosophy - Simmons, A. John (Fundamentals of philosophy series, 2008)
The most recent addition to the Fundamentals of Philosophy Series, Political Philosophy is a concise yet thorough and highly engaging introduction to the essential problems of the discipline. Organized topically and presented in a straightforward manner by an eminent political philosopher, A. John Simmons, it investigates the nature and basis of political authority and the structure and organization of political life. Each chapter focuses on a central problem, considers how it could be addressed, and outlines the various philosophical positions surrounding it. Covering both historical and contemporary work, this unique text offers a survey of major concepts and debates while also reflecting the author's views and contributions. Accessible to novices yet also useful for advanced students, Political Philosophy presents a unified and accessible portrait of the issues that have been puzzling political philosophers for years.